THE INFLUENCE OF USER-GENERATED CONTENT ON BRAND EQUITY AND PURCHASE INTENTION OF THE LAFIYE BRAND AMONG GENERATION Z - Ayun, Tresya Hesi Qurrata; Mutasowifin, Ali (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
The rise of Muslim fashion has prompted local brands to innovate in terms of design and marketing in order to meet the diverse preferences of consumers. User-generated content is a marketing strategy that aims to increase credibility and consumer trust through content created by users. This study aims to determine the effect of user-generated content on brand equity and purchase intention of the Lafiye brand among Generation Z women in the Greater Jakarta area. The research uses a quantitative approach by distributing questionnaires from May to June 2025 in a hybrid manner. The sample in this study consisted of 130 respondents determined using purposive sampling techniques. The data was then analyzed using validity tests, reliability tests, descriptive analysis, and SEM-PLS using Microsoft Excel 2010, SPSS 26, and SmartPLS 4.0 software. The results showed that user-generated content had a positive and significant effect on brand equity and user-generated content had a positive and significant effect on purchase intention. Content that contains positive values and provides benefits to consumers is highly recommended to strengthen brand equity and increase purchase intention.